2019
DOI: 10.1016/j.anai.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The “envirome” and what the practitioner needs to know about it

Abstract: Ambient air pollutant exposure has been associated with development of both asthma and eczema. Mechanistic plausibility for the effect of pollutants on atopy has been shown in sensitization studies with diesel exhaust particles and in epigenetic studies of circulating T cells from children with increased exposure to ambient pollutants. 2. Environmental public policy that reduces pollution has clearly been shown to decrease community risk for asthma and to improve lung function 3. Microbiome studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
1
7
0
2
Order By: Relevance
“…Our results also showed that asthma cases had significantly higher parental smoke exposure and smoking history. This finding once again demonstrated to us the effect of smoke exposure on the pathogenesis of asthma as reported previously [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results also showed that asthma cases had significantly higher parental smoke exposure and smoking history. This finding once again demonstrated to us the effect of smoke exposure on the pathogenesis of asthma as reported previously [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…The immediate consequences (fatalities, emergency room visits, and stress caused by the destruction of homes, livelihoods, and mass evacuations) are readily acknowledged, but little attention has been paid to the less obvious medium-and long-term health effects of wildfires. Of great additional concern is how vulnerable populations, firefighters, pregnant women, children, the elderly, and those from marginalized communities (due to ethnic or socioeconomic status), become at high risk of developing disease upon repeated wildfire exposures [13][14][15]. This review is aimed at discussing these issues in light of currently available information.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-level (tropospheric) O 3 is generated by the action of sunlight's UV rays from precursors (mostly air pollutants containing hydrocarbons, volatile organic compounds [VOC] and nitrogen oxides emitted during fossil fuel combustion). In cities with high O 3 levels people had an over 30% increased risk of dying from lung disease (117) and children playing outdoor sports had a three times greater chance of developing asthma (118,119).…”
mentioning
confidence: 99%